Impact of Abiotic Stress on Antioxidant Enzyme Activity and Physiological Performance of Niger (Guizotia Abyssinica L.) - Singh, Anamika; Perveen, Azra (American Journal of Botany and Bioengineering, 2025)
Niger (Guizotia abyssinica L.) is a significant minor oil seed crop and is cultivated under rainfed and low-input agricultural systems in Bihar where crop productivity is increasingly becoming endangered by abiotic stresses like drought, salinity and temperature extremes. Unpredictable monsoon cycle, prolonged dry season and increasing temperature caused by climate change leads to oxidative stress in plants causing massive physiological and yield losses. The current research is a compilation of existing evidence of experiment to evaluate the impact of abiotic stress on the activity of antioxidant enzymes, biochemical measures of oxidative stress, physiological performance of niger with particular reference to agro-climatic condition of Bihar. Abiotic stresses lead to overproduction of reactive oxygen species (ROS) that leads to lipid peroxidation, chlorophyll degradation and dysfunction of photosynthetic machinery. High malondialdehyde (MDA) content, disturbed chlorophyll fluorescence (Fv/Fm) and reduced photosynthetic rates are significant parameters of oxidative stress in niger plants under stress. To neutralize these effects, niger induces an integrated antioxidant defense mechanism that includes enzymatic antioxidants, including superoxide dismutase, catalase, ascorbate peroxidase and glutathione reductase, and non-enzymatic factors, including proline, ascorbate and glutathione. These responses vary in size and efficiency across genotypes, which highlights the significance of genetic variability in stress tolerance. The biochemical, physiological and molecular indicators can be combined to provide a complete framework of evaluation of the stress responses and the identification of resilient niger genotypes to provide Bihar. These integrated methods and improved agronomic methods and the new biotechnological methods can significantly contribute to the enhancement of stress resilience, the stabilization of oilseed production and the livelihoods of small and marginal farmers in the area.